2013
DOI: 10.3892/etm.2013.999
|View full text |Cite
|
Sign up to set email alerts
|

Free dermatoplasty combined with vacuum sealing drainage for the treatment of large-area soft tissue defects accompanied by bone exposure in the lower leg

Abstract: The aim of this study was to investigate the clinical efficacy of free dermatoplasty combined with vacuum sealing drainage (VSD) for the treatment of large-area soft tissue defects accompanied by bone exposure in the lower leg (crus). Free dermatoplasty combined with VSD was used to treat 36 patients with large-area soft tissue defects accompanied by bone exposure in the lower leg. The areas of the soft tissue defects ranged from 25×12 to 35×30 cm and the areas of exposed bone ranged from 6×4 to 10×6 cm. When … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…It can prevent infection, stimulate granulation, reducing postoperative complications, and improving the success of subsequent surgery. 19 During treatment with the VSD system, the dressing was changed once every 5 days; weekly wound measurements were obtained during the VSD dressing changes. Decreases in the sizes of the wounds were detected each week at the rate of approximately 0.5 to 1 cm in depth and 5 to 10% in wound diameter.…”
Section: Resultsmentioning
confidence: 99%
“…It can prevent infection, stimulate granulation, reducing postoperative complications, and improving the success of subsequent surgery. 19 During treatment with the VSD system, the dressing was changed once every 5 days; weekly wound measurements were obtained during the VSD dressing changes. Decreases in the sizes of the wounds were detected each week at the rate of approximately 0.5 to 1 cm in depth and 5 to 10% in wound diameter.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we found that microskin autografts covered with NPWT exhibited a lower infection rate during removal of the inner layer at first dressing change compared with those covered with the conventional gauze. The biological film of VSD can separate the grafted wound from the outside [13,24]. Moreover, continuous negative pressure draining efficiently clears wound exudation in all directions and alters the environment for bacterial growth, leading to effectively preventing bacterial infection because these fluids act as media for bacteria growth and obstacles for capillary growth [21,25].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the comparative studies on using NPWT and conventional dressing of an open wound with microskin autografts are scarcely reported. Vacuum sealing drainage (VSD; Wuhan Weisidi Inc, Hubei, China) dressing, which is one kind of an NPWT dressing, has become a widely accepted material for treatment of open wounds [12,13]. VSD includes a porous-foam seaweed salt soft pad, which wraps drainage tubes with side holes, the soft pad contacts, and fills the wound defects, which serves as a bridge between wound and drainage tubes.…”
Section: Introductionmentioning
confidence: 99%
“…The number of patients with large-area soft tissue defects accompanied by bone exposure has been increasing due to frequently-occurring road accidents, high-energy explosives, deep burns, work-related injuries and tumor resection ( 1 ). Such wounds are often associated with severe avulsion, infection, and poor blood supply, therefore requiring a long healing time.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibitory effects on bacteria reproduction could largely result from the negative pressure of VSD, which creates a relatively anoxic environment on the wound surface, without affecting the surrounding healthy tissues. Owing to these merits of VSD, surgeons have broadly accepted VSD for treatment of soft tissue trauma ( 1 , 5 , 6 ) and bone-exposed wounds ( 7 9 ). Nonetheless, few comprehensive analyses have investigated the effectiveness and inherent mechanism of VSD treatment for bone-exposed wounds.…”
Section: Introductionmentioning
confidence: 99%